REVIEW OF INFORMATION TECHNOLOGY UPDATE ON QUALITY CONTROL AND QUALITY ASSURANCE OF HALAL PRODUCTS - Muhammad Ridwan Harahap (CYBERSPACE: Jurnal Pendidikan Teknologi Informasi, 2018)
Technological developments are very rapid but it does not necessarily with the renewal of information technology to the public due to the limited differences in public interest. Indonesia is one of the most populous countries in the world with the majority of the Muslim population. In line with that, the Muslim community highly upholds the values of Islamic teachings contained in the Qur'an one of the concept of Halalan Toyyiban. Information that is rarely accepted by the public is the halal principle of an industrial product, whether food, beverage, cosmetic or other manufacturing industries. This is also supported by the human lifestyle factors on goods from outside the country regardless of the origin of the goods. As a predominantly Muslim country, it is necessary to have simple and accurate information on the use of materials in an industrial product to determine the absence of an industrial product. One of them is the use of derived compounds or single compounds derived from pigs. From several research results that have been done, obtained the image pattern from the examination result of the sample. So that people can easily obtain information about the source of materials used in everyday life.